THE PERCEIVED INFLUENCE OF PART-TIME TEACHING ON STUDENTS’ PERFORMANCE IN MICRO-TEACHING CLASS - Siti Khasinah; Yuliar Masna; Anita Siregar (Universitas Islam Negeri Banda Aceh, 2019)
The main objective of this study was to examine the perceived influence of part-time teaching on students’ performance in Micro-Teaching class. A quantitative research approach using questionnaire was carried out to get the view of thirty students of 2014 intake year of Department of English Language Education, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri (UIN) Ar-Raniry Banda Aceh. The findings indicated that students were helped by having part-time teaching through developing skills and confidence, reducing anxiety and fear, developing ability of managing classroom, increasing ability in selecting teaching goals and in preparation of lesson plans, proper worksheet, assessment tools, instructional media, and teaching methods. In addition, it supported them to improve their ability in asking questions and speaking in front of groups as well as to use time effectively. To conclude, part-time teaching has increased students’ skills in micro-teaching class.